Exploring the wavelength range of InP/AlGaInP QDs and application to dual-state lasing. (5th March 2015) - Shutts, Samuel; Elliott, Stella N; Smowton, Peter M; Krysa, Andrey B
Abstract: We explore the accessible wavelength range offered by InP/AlGaInP quantum dots (QD)s grown by metal–organic vapour phase epitaxy and explain how changes in growth temperature and wafer design can be used to influence the transition energy of the dot states and improve the performance of edge-emitting lasers. The self assembly growth method of these structures creates a multi-modal distribution of inhomogeneously broadened dot sizes, and via the effects of state-filling, allows access to a large range of lasing wavelengths. By characterising the optical properties of these dots, we have designed and demonstrated dual-wavelength lasers which operate at various difference-wavelengths between 8 and 63 nm. We show that the nature of QDs allows the difference-wavelength to be tuned by altering the operating temperature at a rate of up to 0.12 nm K −1 and we investigate the factors affecting intensity stability of the competing modes.